2013
DOI: 10.1371/journal.pone.0083600
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Hospitalized Acute Respiratory Infection in Guatemala

Abstract: Acute respiratory infections (ARI) are an important cause of illness and death worldwide, yet data on the etiology of ARI and the population-level burden in developing countries are limited. Surveillance for ARI was conducted at two hospitals in Guatemala. Patients admitted with at least one sign of acute infection and one sign or symptom of respiratory illness met the criteria for a case of hospitalized ARI. Nasopharyngeal/oropharyngeal swabs were collected and tested by polymerase chain reaction for adenovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
39
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 39 publications
12
39
2
1
Order By: Relevance
“…RSV (8.68 ) was the most frequently detected virus in 2015, which was in agreement with reports from southern and eastern China (19,20) and an eastern Mediterranean region (21). However, the most commonly identified virus in 2016 was influenza, similar to another report (22), but different from a report that found HRV to be the most common respiratory virus (23). For the pediatric medicine ward and ICU, influenza was the most prevalent virus among all viral pathogens.…”
Section: Discussionsupporting
confidence: 84%
“…RSV (8.68 ) was the most frequently detected virus in 2015, which was in agreement with reports from southern and eastern China (19,20) and an eastern Mediterranean region (21). However, the most commonly identified virus in 2016 was influenza, similar to another report (22), but different from a report that found HRV to be the most common respiratory virus (23). For the pediatric medicine ward and ICU, influenza was the most prevalent virus among all viral pathogens.…”
Section: Discussionsupporting
confidence: 84%
“…In patients, diagnosed with ARI the most frequently detected virus was HRV -33 (16.75%) ( Table 3). (8)(9)(10)(11)(12). Coinfections in this study were identified in a relatively small percentage of cases (3.15%).…”
Section: Clinical Characteristicsmentioning
confidence: 53%
“…Similar to other regions, in Guatemala, confinement of animals and increased population densities related to commercial farming practices seem to be important in the epidemiology of swine IAV. Other environmental factors that influence IAV transmission in tropical countries like Guatemala are not well defined; in humans the proportion of IAV cases usually reaches a peak during the rainy season (from May to August) and IAV transmission seem to be associated with specific humidity 30, 31, 32. Similar to humans, seasonal infections of IAV in backyard pigs are plausible, whereas in commercial farms, IAV infection may be directly linked to nature of the pig production cycle.…”
Section: Discussionmentioning
confidence: 99%